Experimental Design Approach to Optimize HPLC Separation of Active Ingredients, Preservatives, and Colorants in Syrup Formulation - Dinc-Zor, Sule; Asci, Burge; Donmez, Ozlem Aksu; Hacimustafa, Ozge (OXFORD UNIV PRESS INC, 2019)
Background: Preservatives and colorants in pharmaceutical products may be highly toxic, especially for sensitive individuals, when they are used in excessive amounts. In this context, sensitive and non-labor-intensive analytical methods with short analysis time for simultaneous quantification of these additive substances in drugs can meet all requirements in quality control laboratories. Objective: The aim of the study was to develop a simultaneous HPLC method for the analysis of pseudoephedrine HCl and guaifenesin, along with preservatives, methyl paraben and propyl paraben, and colorants, ponceau 4R and sunset yellow, in a syrup sample. Methods: Optimum conditions of HPLC separation were determined by Box-Behnken experimental design. Four independent variables of the separation were pH (6.0, 6.5, and 7.0) and flow rate of the mobile phase (2.0, 2.2, and 2.4 mL/min) and mobile phase ratios for the first and second gradient elutions (75, 80, and 85% for Gradient 1 and 50, 55, and 60% for Gradient 2 in terms of phosphate buffer percent, respectively). Results: The optimum conditions were found to be pH, 6.3; flow rate, 2.4 mL/min; and mobile phase ratios (phosphate buffer acetonitrile) for Gradient 1 and 2, 85+15 (v/v) and 60+40 (v/v), respectively. Conclusions: Simultaneous analysis of all compounds was achieved by using this HPLC method with a short run time below 10 min. Highlights: This simple, rapid, and validated method is convenient and applicable for routine analysis of pharmaceutical products having similar composition without the need for any extraction step.
Keywords: PARABENS; METHYL; Chemistry; Food Science & Technology